2009
DOI: 10.1021/jm801491w
|View full text |Cite
|
Sign up to set email alerts
|

Conformationally Constrained Peptidomimetic Inhibitors of Signal Transducer and Activator of Transcription 3: Evaluation and Molecular Modeling

Abstract: Signal transducer and activator of transcription 3 (Stat3) is involved in aberrant growth and survival signals in malignant tumor cells and is a validated target for anti-cancer drug design. We are targeting its SH2 domain to prevent docking to cytokine and growth factor receptors and subsequent signaling. The amino acids of our lead phosphopeptide, Ac-pTyr-Leu-Pro-Gln-Thr-Val-NH 2 , were replaced with conformationally constrained mimics. Structure-affinity studies led to the peptidomimetic, pCinn-Haic-Gln-NHB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
75
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(76 citation statements)
references
References 88 publications
(292 reference statements)
1
75
0
Order By: Relevance
“…on April 8, 2019. by guest www.bloodjournal.org From inhibitors is the peptidomimetics, which are relatively potent in vitro 28,29 but historically have carried the challenge of adequate cell permeability. CPA-7, a platinum compound, has been shown to inhibit Stat3 and Stat1 activity and to reduce tumor cell growth.…”
Section: Discussionmentioning
confidence: 99%
“…on April 8, 2019. by guest www.bloodjournal.org From inhibitors is the peptidomimetics, which are relatively potent in vitro 28,29 but historically have carried the challenge of adequate cell permeability. CPA-7, a platinum compound, has been shown to inhibit Stat3 and Stat1 activity and to reduce tumor cell growth.…”
Section: Discussionmentioning
confidence: 99%
“…Although compound 5's hexyl group was not stable enough to maintain the intended conformation, this modification to the inhibitor's structure indicated the potential importance of the pY Ăž 1 pocket. In this regard, Mandal et al have very recently targeted an extended binding cleft including the pY Ăž 1 to pY Ăž 3 sites (occupied by D 706-710 of STAT3) with conformationally constrained peptidomimetic inhibitors (Mandal et al, 2009). Although our targeted binding site involves D 702-706 of STAT3, their findings on the pY Ăž 1 interaction could be helpful in optimizing the core region, which is revealed by our accumulated H-bond mapping results in Figure 10.…”
Section: Comparative Evaluations Of Stat3 Sh2 Inhibitorsmentioning
confidence: 82%
“…So far, there have been several systematic studies on phosphotyrosine peptide interactions with various SH2 domains ) including STAT3-SH2 (Mandal et al, 2009); but there have been no systematic computational study on small molecule interactions with any SH2 domain. To compare their binding potency, specificity, and dynamic nature, this work is to systematically evaluate eight representative STAT3-SH2 inhibitors ( Figure 3) computationally through combined molecular docking and molecular dynamics simulation.…”
Section: The Current Stat3 Sh2 Inhibitors and The Focus Of This Workmentioning
confidence: 99%
“…Extensive studies were carried out to probe the phosphopeptide binding site [64,96–101]. These studies revealed that phosphotyrosine could be replaced by the conformationally constrained 4-phosphocinnamate [99] (e.g., PM-66F, Figure 9) and inclusion of a methyl group on the β-carbon of the cinnamate increased affinity [97]. The central Leu–Pro dipeptide had a trans peptide bond [96] and could be replaced with the tricyclic lactam Haic [99].…”
Section: Peptidomimetic Inhibitors Targeting the Sh2 Domain Of Stat3mentioning
confidence: 99%